MATERI MUATAN UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL DITINJAU DARI ASAS-ASAS PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DAN SIYASAH DUSTURIYAH - Yossy Deslavia; Ulya Atsani; Hebby Rahmatul Utamy (Institut Agama Islam Negeri Batusangkar, 2023)
The purpose of this study is to explain the principles for forming laws and regulations and explain the contents of the TPKS Law from the view of Siyasah Dusturiyah in the formation of the TPKS Law. The type of research used in this research is normative juridical research. The approach taken uses regulatory analysis based on primary legal material by examining theories, concepts, legal principles, and laws and regulations related to the process of forming the TPKS Law, which originate from the 1945 Constitution. This research shows that the principles the principle of forming statutory regulations used in the formation of the TPKS Law are not by the four principles of Formation of statutory regulations, namely: seen from the principle of conformity between types, hierarchies, and content material, it is not appropriate and is considered contrary to Article 29 of the 1945 Constitution. In the view of Siyasah Dusturiyah, in this case, it explains that the rules that are made should aim for benefit, but in the content material of Article 4 paragraph (2) letters d and h, when viewed from the principles of forming legislation, in terms of siyasah dusturiyah, several principles are not according to them, namely: first: the principle of conformity between types, hierarchies, and content material, second: the principle can be implemented, third: the principle of clarity of formulation and fourth: the principle of efficiency and effectiveness